10-10-10 : 10 minutes, 10 months, 10 years - a life-transforming idea - Welch, Suzy. (New York : Scribner, 2009)
From'O, The Oprah Magazine' columnist and coauthor of the #1 bestseller'Winning' comes a powerful new strategy for making difficult decisions and clarifying life choices--when faced with a decision, determine the consequences and outcomes of your various options in 10 minutes, 10 months, and 10 years.
Before sunrise -- In the light of day -- The science behind the system -- The values equation -- The code of love -- On the job -- Charting your career -- Your partner in parenting -- Friendship lost and found -- The mistletoe dart and the circle of life -- The happiness list.
Keywords: Decision making; Problem solving; Self-realization.; Success; Life skills -- Handbooks, manuals, etc